2018
DOI: 10.1186/s12967-018-1443-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on the progression types of cancer in patients with breast cancer undergoing eribulin chemotherapy and tumor microenvironment

Abstract: BackgroundRecently, the concepts of progression due to pre-existing lesions (PPL) and progression due to new metastasis (PNM) have been proposed to differentiate the progression types of treatment-resistant cancers. Previously, the differences between these two progression types did not affect the determination of treatment strategies since both PPL and PNM are classified as progressive disease based on the response evaluation criteria in solid tumors (RECIST) diagnostic criteria. On the other hand, tumor infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…This fact may reflect the inhibitory effect of eribulin in the EMT, reducing cancer cell migration and invasiveness; however, we did not find any information about the pattern of progression in patients who received other oncospecific treatments [13]. It has been previously reported that patients with ABC who develop tumour progression with new metastases have worse outcomes compared to those patients whose disease progresses due to growth of pre-existing lesions [11, 30].…”
Section: Discussionmentioning
confidence: 61%
“…This fact may reflect the inhibitory effect of eribulin in the EMT, reducing cancer cell migration and invasiveness; however, we did not find any information about the pattern of progression in patients who received other oncospecific treatments [13]. It has been previously reported that patients with ABC who develop tumour progression with new metastases have worse outcomes compared to those patients whose disease progresses due to growth of pre-existing lesions [11, 30].…”
Section: Discussionmentioning
confidence: 61%
“…The activation of protooncogenes to the occurrence and development of cancer entails a lot of complex processes that involves multiple factors. These factors are dependent on genetic changes, external cellular pressures, function and regulation of the body's immune system, and the microenvironment of the tissue [ 30 ]. Studies showed that most galectins are involved in the development of various cancers [ 31 , 32 ] and the processes they involved in are mainly tumor cell transformation through interacting with oncogenes such as HRAS and KRAS [ 33 , 34 ].…”
Section: Galectins In Cancermentioning
confidence: 99%
“…S1). Based on previous reports [22, 23], we defined a high TILs density as scores of 2–3 (i.e., > 10%) and a low TILs density as scores of 0–1 (≤ 10%).…”
Section: Methodsmentioning
confidence: 99%